1996
DOI: 10.1111/j.1699-0463.1996.tb00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance mechanisms inSalmonellaspecies causing bacteraemia in Malawi and Kenya

Abstract: In two studies on the causative agents of bacteraemia in Malawi and Kenya, 33 Salmonella strains were isolated. Fourteen strains of Salmonella typhimurium and Salmonella enteritidis were found to exhibit resistance to amoxicillin, amoxicillinklavulanic acid and cotrimoxazole as well as decreased susceptibility to a range of aminoglycosides. The resistant strains were studied to establish their resistance mechanisms. Beta-lactamase co-focusing with TEM-1 was present in 12 strains. In two strains, both S. typhim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Although still effective in vitro, the trend for the three drugs is of concern. Similarly, a high prevalence of multiresistant Typhimurium was reported from Zaire [12], Central Africa [13] and Malawi [15]. In most multiresistant Typhimurium outbreaks in Africa, third-generation cephalosporins and ciprofloxacin were effective in treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although still effective in vitro, the trend for the three drugs is of concern. Similarly, a high prevalence of multiresistant Typhimurium was reported from Zaire [12], Central Africa [13] and Malawi [15]. In most multiresistant Typhimurium outbreaks in Africa, third-generation cephalosporins and ciprofloxacin were effective in treatment.…”
Section: Discussionmentioning
confidence: 95%
“…For example, previously in Kenya [ 15,171 Typhimurium isolates from cases of bacteraemia were also shown to be multiresistant to most commonly available drugs. In addition, in the present study 31.3% of the isolates showed decreased susceptibility to co-amoxiclav, gentamicin and nalidixic acid.…”
Section: Discussionmentioning
confidence: 99%
“…tested had also resistance against some other antimicrobial agents like cotrimoxazole (trimethoprim-sulfamethoxazole) 14 (38.9%) and cefoxitin 11 (30.6) which is in agreement with studies in Debre-Zeit and Addis Ababa, Ethiopia (Bayleyegn et al, 2003a) and in sub-Saharan Africa. This is maybe due to unselective and prevalent uses of the frequently existing antimicrobials both in the veterinary and public health practices since, in these countries, people have easy access to various antimicrobials and can purchase them without prescription (Leegaard et al, 1996). Thus, the present report contradicts with the study of Forough et al (2012), which indicated that Salmonella isolates from Iran showed that Salmonella were resistant to chloramphenicol (21.42%), ampcillin (42.58%), and tetracycline (42.58%).…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…In line with this, resistance for two or more of antimicrobials which was observed in this study was lower than other study conducted in Addis Ababa, Ethiopia (Zelealem et al, 2011). This could be credited mainly to the unselective use and abuse of antimicrobials both in the farm and human health sectors (Leegaard et al, 1996;Bayleyegn et al, 2003a).…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…The issue of antimicrobial resistance is more complex in developing countries (Leegaard et al 1996) like Ethiopia where Salmonella is not routinely isolated and resistance to commonly used antimicrobial drugs in veterinary and public health sector not regularly assessed. Therefore, the present study, which was a part of cross-sectional study of Salmonella from supermarket food items and personnel, was undertaken to investigate the susceptibility of Salmonella isolates to commonly used antimicrobial agents in Ethiopia for the treatment of bacterial diseases including salmonellosis.…”
Section: Introductionmentioning
confidence: 99%